2019
DOI: 10.1177/0706743719874181
|View full text |Cite
|
Sign up to set email alerts
|

Hypoactivity in the Paraterminal Gyrus Following Bilateral Anterior Capsulotomy

Abstract: Objective: Bilateral anterior capsulotomy (BAC) is one of the ablative neurosurgical procedures used to treat major depressive disorder or obsessive-compulsive disorder when all other therapies fail. Tristolysis, a reduction in sadness, is the most striking clinical effect of BAC and is seen in the first 1 to 2 weeks after surgery. This retrospective study measured regional cerebral blood flow (rCBF) following surgery to identify which cortical regions were impacted and could account for this clinical effect. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…After applying our inclusion criteria, ten unique studies [31][32][33][34][35][36][37][38][39] remained to be used for meta-analysis. Four studies [15,19,40,41] contained duplicate data and this information was extracted and included when missing from the original studies, as shown in online supplementary C-Table 1 [50][51][52][53][54][55][56][57][58][59][60][61].…”
Section: Systematic Search Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After applying our inclusion criteria, ten unique studies [31][32][33][34][35][36][37][38][39] remained to be used for meta-analysis. Four studies [15,19,40,41] contained duplicate data and this information was extracted and included when missing from the original studies, as shown in online supplementary C-Table 1 [50][51][52][53][54][55][56][57][58][59][60][61].…”
Section: Systematic Search Resultsmentioning
confidence: 99%
“…Like the Vancouver group, they also noted the tristolytic effect. Tristolysis is a rapid reduction in depression surfacing as early as 1-week post-ablation when BAC is used to treat TRD, which may be the marker of an effective capsulotomy [19, 41].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…An increasing line of evidence suggests that increasing the motivation to expend cognitive effort, rather than enhancing cognitive networks themselves, would be more effective in bolstering goal-directed behaviour [33] . Thus, if frontostriatal circuitry can be mapped and effectively modulated post-craniotomy, this would be a significant advancement and become important for other areas of neurosurgery, such as limbic surgery [34] .…”
Section: Connectome-based Stimulation For Cognitive Rehabilitationmentioning
confidence: 99%